2018
DOI: 10.1177/1178223418782904
|View full text |Cite
|
Sign up to set email alerts
|

Change in Breast Cancer Screening Knowledge is Associated With Change in Mammogram Intention in Mexican-Origin Women After an Educational Intervention

Abstract: Purpose:To determine the relationship between breast cancer screening knowledge and intent to receive a mammogram within 6 months in a sample of Mexican-origin women living in El Paso, Texas.Methods:A total of 489 uninsured Mexican-origin women were assigned to treatment or control and completed surveys at pre- and postintervention. Pre-post associations between breast cancer screening knowledge and intent were tested.Results:Participants were on average were 56.7 years of age and spoke primarily Spanish (92.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…[11][12][13] Studies have shown that women who are more knowledgeable about BC and benefits of screening are more likely to participate in screening programs. 14,15 Educational interventions have proven to be effective in increasing the knowledge of BC and practice of breast self-examination. [16][17][18][19] Very few studies have been conducted in UAE assessing the knowledge of BC and its screening in the Arab women.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Studies have shown that women who are more knowledgeable about BC and benefits of screening are more likely to participate in screening programs. 14,15 Educational interventions have proven to be effective in increasing the knowledge of BC and practice of breast self-examination. [16][17][18][19] Very few studies have been conducted in UAE assessing the knowledge of BC and its screening in the Arab women.…”
Section: Introductionmentioning
confidence: 99%